Effective mRNA Protection by Poly(l‐ornithine) Synergizes with Endosomal Escape Functionality of a Charge‐Conversion Polymer toward Maximizing mRNA Introduction Efficiency. Issue 12 (18th March 2022) - Dirisala, Anjaneyulu; Uchida, Satoshi; Li, Junjie; Van Guyse, Joachim F. R.; Hayashi, Kotaro; Vummaleti, Sai V. C.; Kaur, Sarandeep; Mochida, Yuki; Fukushima, Shigeto; Kataoka, Kazunori
Abstract: For efficient delivery of messenger (m)RNA, delivery carriers need two major functions: protecting mRNA from nucleases and translocating mRNA from endolysosomes to the cytoplasm. Herein, these two complementary functionalities are integrated into a single polyplex by fine‐tuning the catiomer chemical structure and incorporating the endosomal escape modality. The effect of the methylene spacer length on the catiomer side chain is evaluated by comparing poly(l ‐lysine) (PLL) with a tetramethylene spacer and poly(L‐ornithine) (PLO) with a trimethylene spacer. Noteworthily, the nuclease stability of the mRNA/catiomer polyplexes is largely affected by the difference in one methylene group, with PLO/mRNA polyplex showing enhanced stability compared to PLL/mRNA polyplex. To introduce the endosomal escape function, the PLO/mRNA polyplex is wrapped with a charge‐conversion polymer (CCP), which is negatively charged at extracellular pH but turns positive at endosomal acidic pH to disrupt the endosomal membrane. Compared to the parent PLO/mRNA polyplex, CCP facilitated the endosomal escape of the polyplex in cultured cells to improve the protein expression efficiency from mRNA by approximately 80‐fold. Collectively, this system synergizes the protective effect of PLO against nucleases and the endosomal escape capability of CCP in mRNA delivery. Abstract : Ribonuclease protection and endosomal escape functionalities are integrated into a single polyplex for efficient mRNA delivery. Complexing mRNA using poly(L‐ornithine) (PLO) provides enhanced mRNA protection against the serum compared to poly(l ‐lysine). Coating of PLO/mRNA polyplex with an anionic charge‐conversion polymer (CCP) substantially facilitates the endosomal escape, where CCP is converted to a positively charged polymer in the endosomal acidic pH to facilitate the endosomal disruption.